Construction of a novel choline metabolism-related signature to predict prognosis, immune landscape, and chemotherapy response in colon adenocarcinoma - Liu, Cong; Liu, Dingwei; Wang, Fangfei; Liu, Yang; Xie, Jun; Xie, Jinliang; Xie, Yong (Frontiers in Immunology, 2022)
Background: Colon adenocarcinoma (COAD) is a common digestive system malignancy with high mortality and poor prognosis. Accumulating evidence indicates that choline metabolism is closely related to tumorigenesis and development. However, the efficacy of choline metabolism-related signature in predicting patient prognosis, immune microenvironment and chemotherapy response has not been fully clarified. Methods: Choline metabolism-related DEGs between normal and COAD tissues were screened using datasets from TCGA, KEGG, AmiGO2 and Reactome Pathway databases. Two choline metabolism-related genes were identified by univariate and multivariate Cox regression analyses. TCGA-COAD was the training cohort, and GSE17536 was the validation cohort. Patients in the high- and low-risk groups were distinguished according to the optimal cutoff value of the risk score. A nomogram was used to assess the prognostic accuracy of the signature. The distribution and expression of CHKB and PEMT in various types of immune cells were analyzed based on scRNA-seq. CIBERSORT and ESTIMATE algorithms evaluated immune cell infiltration. Evaluation of IC50 of common chemotherapeutic drugs was performed. Small molecule compounds were predicted using CMap database. The expression of CHKB and PEMT were detected by immunohistochemistry, Western blot, and qRT-PCR. Results: We constructed and validated choline metabolism-related signature containing two genes (CHKB and PEMT). The OS of patients in the high-risk group was significantly worse than low-risk group. The nomogram could effectively and accurately predict the OS of patients. The DCA curve and CIC demonstrate the clinical utility of the nomogram. scRNA-seq showed that CHKB was mainly distributed in endothelial cells, while PEMT was mainly distributed in CD4+ T cells and CD8+ T cells. There were significant differences in the immune microenvironment, immune checkpoint expression and chemotherapy response between the two risk groups. Finally, we found that the expression levels of CHKB were elevated in normal samples, whereas those of PEMT were increased in COAD samples. Conclusion: In conclusion, we constructed a choline metabolism-related signature in COAD and revealed its potential application value in predicting the prognosis, immune microenvironment, and chemotherapy response of patients, which may lay an important theoretical basis for future personalized precision therapy.